1994
DOI: 10.1017/s0022112094001370
|View full text |Cite
|
Sign up to set email alerts
|

Local isotropy in turbulent boundary layers at high Reynolds number

Abstract: To test the local-isotropy predictions of Kolmogorov's (1 941) universal equilibrium theory, we have taken hot-wire measurements of the velocity fluctuations in the testsection-ceiling boundary layer of the 80 x 120 foot Full-Scale Aerodynamics Facility at NASA Ames Research Center, the world's largest wind tunnel. The maximum Reynolds numbers based on momentum thickness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

88
537
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(631 citation statements)
references
References 24 publications
88
537
5
1
Order By: Relevance
“…Because the flow in the inertial subrange is locally homogeneous and isotropic, the scalar wavenumber K can be reasonably approximated by its one-dimensional longitudinal cut as earlier noted. A number of studies have also shown that inertial subrange scaling laws are not sensitive to the local isotropy assumption [20]. Stated differently, inertial subrange scaling laws extend over a much broader range of K values within the inertial subrange when compared to the range of K values inferred from locally-isotropic predictions of velocity components' spectral ratios.…”
Section: A Background and Definitionsmentioning
confidence: 99%
“…Because the flow in the inertial subrange is locally homogeneous and isotropic, the scalar wavenumber K can be reasonably approximated by its one-dimensional longitudinal cut as earlier noted. A number of studies have also shown that inertial subrange scaling laws are not sensitive to the local isotropy assumption [20]. Stated differently, inertial subrange scaling laws extend over a much broader range of K values within the inertial subrange when compared to the range of K values inferred from locally-isotropic predictions of velocity components' spectral ratios.…”
Section: A Background and Definitionsmentioning
confidence: 99%
“…Yet, questions remain and laboratory experiments in a single facility in which the boundary conditions are well controlled are few. Using an inertial-subrange scaling that enables use of a linear ordinate, Saddoughi & Veeravalli (1994) were able to show that the inertial subrange and local isotropy do not necessarily coincide -see also Mestayer (1982). Of the two decades exhibiting a -5/3 slope on log-log axes, only the higher one had a spectral shear correlation coefficient approaching zero.…”
Section: Introductionmentioning
confidence: 99%
“…Dual studies are limited, notable exceptions in shear flows being Saddoughi & Veeravalli (1994); Mydlarski & Warhaft (1996), among others. Many of the ambiguities associated with the definition of the −5/3 inertial subrange law might be clarified by appeal to a unifying physical process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small level of anisotropy in ε u i u j for z/δ > 0.1 can be attributed to the relatively low Reynolds number of the DNS of Spalart (1988). For a rough-wall boundary layer, the experiments of Saddoughi and Veeravalli (1994) and Saddoughi (1997) confirm that at this altitude there is also local isotropy of ε u i u j at high Reynolds numbers. Some studies even conclude that the roughness increases the degree of isotropy closer to the wall and this impact is greater with three-dimensional roughness .…”
Section: U 2 Evolution Equationmentioning
confidence: 76%